Infection History and Current Coinfection With Schistosoma mansoni Decreases Plasmodium Species Intensities in Preschool Children in Uganda. (5th March 2022) - McDowell, Daniel; Hurt, Lisa; Kabatereine, Narcis B; Stothard, John Russell; Lello, Joanne
Abstract: Malaria–schistosomiasis coinfections are common in sub-Saharan Africa but studies present equivocal results regarding the interspecific relationships between these parasites. Through mixed-model analyses of a dataset of Ugandan preschool children, we explore how current coinfection and prior infection with either Schistosoma mansoni or Plasmodium species alter subsequent Plasmodium intensity, Plasmodium risk, and S mansoni risk. Coinfection and prior infections with S mansoni were associated with reduced Plasmodium intensity, moderated by prior Plasmodium infections, wealth, and host age. Future work should assess whether these interactions impact host health and parasite control efficacy in this vulnerable age group. Abstract : Plasmodium-Schistosoma mansoni coinfections are associated with a reduced Plasmodium intensity in preschool-aged children. This relationship, however, is modified by prior infections, host age, and family wealth.